India’s Soft Power as a Pillar of Foreign Policy - Aadil Ahmad Shairgojri (HM Journals, 2021)
The power dynamics of nation-states around the world have undergone a significant change in the twenty-first century with regard to how governments define and demonstrate their authority. Since today's political world is becoming increasingly interconnected, governments have no choice but to spend heavily in both their soft and hard power matrices. Because of the current state of world politics, India has a better chance than ever before of becoming a major player in international affairs. In India and around the world, the election of Prime Minister Narendra Modi has caused a sea change in public opinion about the dangers of religious militarism. These rights have become increasingly popular due to the increase of Hindutva rights.